Geospatial Analysis of Elephant Migration from Hwange National Park, Zimbabwe, 2009-2017 - Wickramasooriya, Ashvin; Prarthana, Sanduni (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Hwange National Park, the largest national park in Zimbabwe, has been recorded as experiencing elephant migrations to neighbouring Botswana for several years due to drought-related dryness of water bodies. The adverse impacts of climate change have led to a rise in Zimbabwe's annual mean surface temperature, rendering the country more susceptible to drought conditions and decreased rainfall. To investigate the directional trend of elephant migration patterns from Hwange National Park to neighbouring Botswana, spatiotemporal analysis was conducted from 2009 to 2017 using ArcGIS Pro software. Secondary data was utilized for analysis, with elephant migration data abstracted from Movebank, an open-source data portal for large collections of animal tracking data. These migration patterns were remotely tracked through GPS sensors. Additionally, annual mean surface temperature data, sourced from the International Monetary Fund's climate data, was considered an allied factor with the fundamental objective of the research. A bar chart was created to represent the temperature data statistically. The results emphasized that annual mean surface temperature fluctuations in Zimbabwe have influenced elephant migration, with high surface temperatures recorded in 2010, 2015, and 2016 accompanied by increased migrations. Consequently, the elephants' tendency to migrate towards Botswana has gradually risen throughout the period, underscoring the adverse impacts of climate change.